Penggunaan Abu Sekam Kopi dan Ordinary Portland Cement terhadap Kuat Tekan Beton Normal - Citra SZ, Keumala; Meillyta, Meillyta; Tonayu HSB, Nauly (Tameh, 2022)
Cement is one of the binders which is commonly used as a concrete-forming material. Currently, there is a lot of coffee husk waste in Takengon, Central Aceh Regency, which contains silica. The basis of using coffee husk ash and OPC cement as an adhesive on the normal compressive strength of concrete. This study aims to determine the influence of using coffee husk ash and OPC cement as an adhesive on the compressive strength of normal concrete at a percentage of 5%, 10% and 15%. The research specimen is cylindrical shape with 15 cm diameter and 30 cm height. The test was carried out at the age of 7 and 28 days by using a compressive strength testing machine. The method of making the specimen is in accordance with the SNI 7656-2012 standard. It is found from the results in the laboratory, coffee husk ash obtains silicate compounds (SiO2) 29.11%, magnesium oxide (MgO) 4.92%, calcium oxide (Cao) 5.33%, ferrioxide (Fe2O3) 4.25% and aluminum oxide (Al2O3). The average compressive strength test results of 7-day old concrete at the percentage of 5% coffee husk ash mixture was 20.21 MPa, at 10% was 20.03 MPa and at 15% was 17,25 MPa. The average compressive strength of concrete at 28 days of age with 5% coffee husk ash mixture is 20.27 MPa at 10% coffee husk ash mixture percentage 19.70 MPa and 15% coffee husk ash mixture 15.46 MPa. Comparison of the results of the compressive strength test for concrete at 7 and 28 days was higher for concrete at 7 days. The results of the different compressive strength tests between the ages of the concrete are caused by the high percentage of coffee husk ash mixture where the higher the coffee husk ash percentage, the weaker the adhesion to the concrete. The percentages of coffee husk ash and OPC cement that meet the design compressive strength of 20 MPa are at 5% and 10% respectively.